Thermo-optic multimode interference switches with air and silicon trenches - M. Al-hetar, Abdulaziz; Yulianti, I.; Mohd Supa'at, Abu Sahmah; Mohammad, Abu Bakar (Elsevier, 2008)
A novel thermo-optic multimode interference (MMI) switch with air and silicon trenches was proposed, and the performance of the switch was simulated. In the design, one heating electrode is used to alter the refractive index at a spot image which changes the phase of this image to realize the switching function. The simulation results clearly indicate that the MMI switch can satisfy âˆ’39 dB crosstalk at two states. The electric power consumption for the MMI switch with these trenches is less than half of that of a conventional MMI switch.